Supply of the industrial products in Romania: A territorial approach - Adriana Grigorescu; Andrea S\~aseanu (Contemporary Economics, 2008)
The industrial products and services supply was analyzed in the present paper through the statistical indicators of the industrial production, applied for Romania (2005), both at macroeconomic and regional level (on development regions). The first part of the paper presents some of the methodological reglamentations used in determining theindustrial production statistical indicator, according to the European Union statistical practices (Pack, 2000; ***ìMethodology of short-term business statisticsî, 2006; Peneder, 2001). In the second part of the paper, the authors analyze the main industrial policy previsions in Romania in order to accelerate the process of resource allocation among and within the various sectors, to improve the competitiveness, to attenuate the discrepancies between the economic development level of Romanian regions and to become part of a common European industrial policy. Regional analysis is a domain largely studied by Kangas, Leskinen, Kangas, 2007; Leskinen, Kangas, 2005; Rondinelli, 1996; Banai-Kashani, Reza, 1989.
Keywords: 330